2011
DOI: 10.12968/jpar.2011.3.9.510
|View full text |Cite
|
Sign up to set email alerts
|

Determining the paediatric educational needs of prehospital providers: part 2

Abstract: Caring for paediatric patients presents unique challenges to prehospital personnel who may have limited training, experience and confidence caring for children. These challenges exist worldwide. Specific recommendations for paediatric educational content and learning strategies are lacking. The purpose of this study was to characterize the paediatric educational needs, barriers, and preferences of prehospital providers in Oregon and to examine these findings in the context of international emergency medical se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…One previous study used qualitative research methods to evaluate pediatric EMS education. 32,33 The findings of this study are consistent with the previous study in describing barriers of cost, distance, and time for rural EMS providers who seek…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…One previous study used qualitative research methods to evaluate pediatric EMS education. 32,33 The findings of this study are consistent with the previous study in describing barriers of cost, distance, and time for rural EMS providers who seek…”
Section: Discussionsupporting
confidence: 90%
“…Finally, the findings are consistent with and complement a recent national report, the 2011 National EMS Assessment 34 . This report highlighted multiple pediatric equipment and communication deficiencies, including: (1) the lack of pediatric specific equipment on ambulances; (2) insufficient attempts by EMS teams to contact medical direction when treating a pediatric patient; and (3) the lack of hospital capability of treating pediatric trauma patients (only 28% nationally).…”
Section: Discussionsupporting
confidence: 81%
“…Two articles identified exposure to children as a beneficial form of education, whether through parenthood or placements in local schools, paediatrician clinics or paediatric hospitals (18,35). All articles examined barriers to paediatric education, the most common being cost, time and quality of training (18,(32)(33)(34)(35).…”
Section: Identifying Educational Needs and Preferencesmentioning
confidence: 99%
“…Both subjective focus group studies and objective surveybased studies found that paramedics are less comfortable with paediatric patients than adults (18,32,33). In Fleischman et al's (32) survey of 219 pre-hospital care providers, 72% of respondents reported feeling less than 'comfortable' across 17 topics in paediatric care.…”
Section: Identifying Educational Needs and Preferencesmentioning
confidence: 99%
See 1 more Smart Citation